The Dairyman's Daughter - Richmond, Legh, 1772-1827 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Dairyman's Daughter" by Legh Richmond is a Christian religious booklet published in 1814. This narrative recounts the spiritual transformation of Elizabeth Wallbridge, a young woman from the Isle of Wight who changed from a worldly life to deep religious devotion after hearing a sermon. During her final illness, Richmond visited and conversed with her, inspiring him to write this account. The booklet became extraordinarily popular, circulating over four million copies in nineteen languages by 1828, with conversions attributed to its influence numbering in the thousands. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Dairyman%27s_Daughter
Release date is 2006-10-24
Transcribed from the Alexander Hislop & Company edition by David Price
Keywords: Christian life -- Juvenile fiction; Conversion -- Christianity -- Juvenile fiction